Public-private Partnership in the Context of Realisation of the State Financial Policy - Ostapenko Victoriia M. (Bìznes Inform, 2014)
In the result of the study the article analyses modern tendencies of development of economy of Ukraine. It marks out problems connected with realisation of the state financial policy. It considers the essence of the state financial policy, its directions (such as budget-tax and monetary-credit), structural components and tasks. It emphasises the place of the public-private partnership as an instrument of realisation of the financial policy. It justifies tasks in the process of realisation of goals of the modern financial policy, which could be carried out with the help of the public-private partnership. The prospect of further studies in this direction is formation of practical recommendations on the use of the public-private partnership in the process of realisation of the state financial policy. Further improvement of the public-private partnership is connected with development of efficient mechanisms of its introduction and optimisation of its financial structure.